Persepsi Masyarakat terhadap Perbandingan Kriteria Harga Kerbau di Kabupaten Mamasa Propinsi Sulawesi Barat - Andi Muhammad Agriawan Suryaalim; Andi Fausiah (Fakultas Pertanian, Universitas Timor, 2023)
The price of buffalo in Mamasa Regency is determined by several unique physical criteria compared to other livestock. Each criterion has a different value when compared to one another, this is very closely related to the socio-cultural system of the Mamasa people. This study aims to describe the perceptions of traders and farmers on several price criteria for buffalo in Mamasa Regency, specifically performance criteria, skin and buffalo horn in price setting. The benefit of knowing this is that there is a quantitative and rational basis in the process of buying and selling buffalo, so that all parties can understand and transparancy. This research approach was mostly carried out quantitatively descriptively by assessing pairwise comparisons through questionnaires. The data was collected in Mamasa District, Mamasa Regency, West Sulawesi in June-July 2022. Based on the results of the data analysis, the highest criterion was buffalo performance, while the second and third respectively were buffalo skin and horn assessment. As for the comparison process, based on the criteria derived from the skin, the priority is skin color compared to hair swirls. Furthermore, the comparison of the horn derivative criteria that is more prioritized is the length of the horn compared to the type or shape of the horn.